2022
DOI: 10.3390/biom12121759
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy Side Effects: Comprehensive Proteomic Study Unraveled Neural Stem Cell Degenerative Differentiation upon Ionizing Radiation

Abstract: Cranial radiation therapy is one of the most effective treatments for childhood brain cancers. Despite the ameliorated survival rate of juvenile patients, radiation exposure-induced brain neurogenic region injury could markedly impair patients’ cognitive functions and even their quality of life. Determining the mechanism underlying neural stem cells (NSCs) response to irradiation stress is a crucial therapeutic strategy for cognitive impairment. The present study demonstrated that X-ray irradiation arrested NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…Temporal lobe necrosis is a late-stage complication that occurs after radiation therapy and, if aggravated, is accompanied by headaches, dizziness, and cognitive impairment, which can be a precursor to dementia [24]. In addition, an in vitro experimental study to investigate the effect of radiation on the regeneration of neural cells reported that radiation arrested the cell cycle of neural stem cells and impacted cellular differentiation [27]. Based on these previous studies, it can be considered that radiation therapy may cause damage to the temporal lobe and interfere with neural regeneration, thereby affecting cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Temporal lobe necrosis is a late-stage complication that occurs after radiation therapy and, if aggravated, is accompanied by headaches, dizziness, and cognitive impairment, which can be a precursor to dementia [24]. In addition, an in vitro experimental study to investigate the effect of radiation on the regeneration of neural cells reported that radiation arrested the cell cycle of neural stem cells and impacted cellular differentiation [27]. Based on these previous studies, it can be considered that radiation therapy may cause damage to the temporal lobe and interfere with neural regeneration, thereby affecting cognitive function.…”
Section: Discussionmentioning
confidence: 99%